Neurokinin-1 Receptor Antagonist Treatment in Polymicrobial Sepsis: Molecular Insights - Akhil Hegde; Yung-Hua Koh; Shabbir M. Moochhala; Madhav Bhatia (International Journal of Inflammation)
Neurokinin-1 receptor blocking has been shown to be beneficial against lung injury in polymicrobial sepsis. In this paper, we evaluated the possible mediators and the mechanism involved. Mice were subjected to cecal ligation and puncture (CLP-) induced sepsis or sham surgery. Vehicle or SR140333 [1 mg/kg; subcutaneous (s.c.)] was administered to septic mice either 30 min before or 1 h after the surgery. Lung tissue was collected 8 h after surgery and further analyzed. CLP alone caused a significant increase in the activation of the transcription factors, protein kinase C-α, extracellular signal regulated kinases, neurokinin receptors, and substance P levels in lung when compared to sham-operated mice. SR140333 injected pre- and post surgery significantly attenuated the activation of transcription factors and protein kinase C-α and the plasma levels of substance P compared to CLP-operated mice injected with the vehicle. In addition, GR159897 (0.12 mg/kg; s.c.), a neurokinin-2 receptor antagonist, failed to show beneficial effects. We conclude that substance P acting via neurokinin-1 receptor in sepsis initiated signaling cascade mediated mainly by protein kinase C-α, led to NF-κB and activator protein-1 activation, and further modulated proinflammatory mediators.